Assessing the equity of a general hiring credit - Lee, Ha Kyeong (KDI School, 2016)
This study aims to analyze inequity of a general hiring credit program, particularly on the consequential marginalization of the most disadvantaged workers upon its implementation. While a general hiring program is slowly gaining popularity as an efficient counter-cyclical measure in the aftermath of the Great Recession, it is likely to be inequitable, discriminating the most disadvantaged workers with visible disabilities. The depreciation arises via two channels: changes in the relative costs of hiring the hard-to-be-employed workers and the stigmatization they must bear to continue disclosing their eligibility status to a categorical hiring credit. To verify them, we take a theoretical approach via a game theory and a search-and-matching models to examine a worker’s relative employability and willingness to participate in the labor market based on his degree of disability before and after the implementation of a general hiring credit program. The results suggest that the implementation of a general hiring credit program (1) induces an outflow of the better-skilled workers from participating in a categorical hiring credit programs, (2) increases the stigma the most underprivileged workers face, and (3) aggravates the latter’s rent from working and an employer’s costs to hire the latter. Furthermore, (4) the employer’s rent reduces even faster when the outflow accelerates.
Thesis(Master) --KDI School:Master of Public Policy,2016